Ensemble Modeling of Antarctic Macroalgal Habitats Exposed to Glacial Melt in a Polar Fjord - Jerosch, Kerstin; Scharf, Frauke K.; Deregibus, Dolores; Campana, Gabriela L.; Zacher, Katharina; Pehlke, Hendrik; Falk, Ulrike; Hass, H. Christian; Quartino, Maria L.; Abele, Doris (Frontiers in Ecology and Evolution, 2019)
Macroalgae are the main primary producers in polar coastal regions and of major importance for the associated heterotrophic communities. On King George Island/Isla 25 de Mayo, West Antarctic Peninsula (WAP) several fjords undergo rapid glacial retreat in response to increasing atmospheric temperatures. Hence, extended meltwater plumes laden with suspended particulate matter (SPM) are generated that hamper primary production during the austral summer season. We used ensemble modelling to approximate changes in the benthic productivity of an Antarctic fjord as a function of SPM discharge. A set of environmental variables was statistically selected and an ensemble of correlative species-distribution models was devised to project scattered georeferenced observation data to a spatial distribution of macroalgae for a “time of measurement” (“tom”) scenario (2008-2015). The model achieved statistically reliable validation results (true scale statistics 0.833, relative operating characteristics 0.975) and explained more than 60% of the modeled macroalgae distribution with the variables “hard substrate” and “SPM”. This “tom” scenario depicts a macroalgae cover of approx. 8% (63 ha) for the total study area (8 km2) and a summer production of approximately 350 t dry weight. Assuming a linear increase of meltwater SPM load over time, two past (1991 and 1998) and two future (2019 and 2026) simulations with varying SPM intensities were applied. The simulation using only 50% of the “tom” scenario SPM amount (simulating 1991) resulted in an increased macroalgal distribution (143 ha) and a higher summer production (792 t) compared to the “tom” status and could be validated using historical data. Forecasting the year 2019 from the “tom” status, an increase of 25% SPM results in a reduction of macroalgae summer production of approximately 60% (141 t). We present a first quantitative model for changing fjordic macroalgal production under continued melt conditions at WAP. As meltwater influenced habitats are extending under climate change conditions, our approach can serve to approximate future productivity shifts for extended WAP fjord systems. The reduction of macroalgal productivity as predicted for Potter Cove may have significant consequences for polar coastal ecosystems as climate change continues.